UJARAN KEBENCIAN (HATE SPEECH) DI MASYARAKAT DALAM KAJIAN TEOLOGI - Zulkarnain Zulkarnain (UIN Sumatera Utara Medan, 2020)
AbstractThe development of sophisticated social media can post content in the form of text, video, sound and images freely which can be disseminated anywhere and anytime with the help of the internet network. Not infrequently social media users abuse social media as a means to vent their emotions, spread false news, bring down others, and even spread hatred to other people or groups. Not a few people who feel disadvantaged as a result of this hate speech. The author's purpose in raising this phenomenon is to find out how hate speech (hate speech) is in society according to theological studies. Methodologically, this study uses a qualitative research type with a library research approach. The factors that cause the perpetrators to do hate speech (hate speech), namely, factors from within the individual (internal) including the psychological and psychological condition of the individual and factors from outside the individual, namely environmental factors, factors of lack of social control, factors of community interest, factors of ignorance community, as well as facilities, facilities and technological and psychological or psychological progress of the actors, namely high emotional power, besides the factors of facilities, facilities and technological progress are also very influential because of the availability of facilities and facilities that are easily available and increasingly sophisticated technological advancements making it easier for each social media users access all information without limits. Efforts to overcome the occurrence of hate speech (hate speech) crime in social media that consists of penal and non-penal efforts. Where penalties consist of imposing sanctions on perpetrators by imprisonment in accordance with what has been stipulated in the ITE Law to provide a deterrent effect. While the non-penal effort is to provide counseling or outreach to the general public regarding information on the impact of electronic media if not used wisely, the ethics of using social media by providing legal knowledge about the ITE Law. Keywords: Speech, Hate, Society, Theology